In-fiber Mach-Zehnder interferometer based on hollow optic fiber for metal ion detection - Liu, Ming-Fu; Wang, Jia-Wei; Hwang, Shug-June (Optics express, 2022)
A new, to the best of our knowledge, in-fiber Mach–Zehnder interferometric sensor is proposed and experimentally demonstrated for detecting Cu 2+ ions in an aqueous environment. The sensor is fabricated simply and cost-effectively by arc-fusing a short section of hollow optical fiber between two standard single-mode fibers and is functionalized by depositing chitosan and poly(acrylic acid) bilayers using electrostatic self-assembly. The proposed sensor shows a linear response with sensitivity of 42 nm/mM in the Cu 2+ ion concentration from 0 to 40 µM. Moreover, the fiber sensor exhibits good reusability and repeatability and is a promising candidate for contamination detection in drinking water and industrial waste water.